FINANCIAL GOVERNANCE TRAINING FOR SMEs BINJAI TOFU VILLAGE: BUILDING A FOUNDATION TOWARDS EDUCATIONAL TOURISM VILLAGE IN NORTH SUMATRA - Ngatemin, Ngatemin; Emrizal, Emrizal; Darmawan, Rahmat; Rosari, Dina (MSJ : Majority Science Journal, 2025)
This study aims to analyze the effectiveness of financial governance training in improving the capacity of MSMEs in Kampung Tahu, Binjai, as a foundation for developing educational tourism villages in North Sumatra. The training focused on improving financial literacy, structured record-keeping practices, separating business and personal finances, and adopting simple financial technology. The methods used were pre-test and post-test surveys, observations, and focus group discussions with a purposively selected sample of 20 MSMEs. Furthermore, data analysis was conducted using the Structural Equation Modeling Partial Least Square (SEM PLS) approach to test the effect of training, financial literacy, technology adoption, and mentoring on financial governance implementation. The results showed a significant increase in financial literacy scores, record-keeping practices, and financial separation after the training. However, adoption of digital financial applications remains limited due to digital literacy and infrastructure constraints. GAP analysis demonstrates the need for ongoing mentoring, infrastructure strengthening, and multi-stakeholder collaboration to bridge the gap between actual and ideal conditions. This training is recommended as a model for developing the capacity of MSMEs based in educational tourism villages, particularly in rural areas facing similar challenges.